The Effect of E-Commerce on Gross Regional Domestic Product and Clustering of Its Characteristics by Utilizing Official Statistics and Big Data - Widhelia Echa Pramesthy; Putri Muthi’ah Dini; Muhammad Amirul Budiman; Zul Ahmad Esharja; Fitri Kartiasih (Journal of Economics, Business, and Accountancy Ventura, 2024)
The objective of this study is to examine the impact of e-commerce on Gross Regional Domestic Product (GRDP) and categorize GRDP according to e-commerce features in 17 provinces throughout Java, Sumatra, and Bali. The Human Development Index (HDI), which measures people's proficiency with technology—among which is e-commerce—is greatest on these three islands. This study makes use of big data in the form of Google Trends data as well as official statistics data obtained from the BPS-Statistics Indonesia. K-means clustering and regression analysis are the research methods employed. The study's findings demonstrate that the three islands' GDP growth rates are considerably accelerated by e-commerce companies. There were two ideal clusters identified: the low and high GRDP clusters. All of the provinces on the island of Java are included in the high cluster, with the exception of Central Java, which is distinguished by high transaction values and e-commerce-related keyword searches. Provinces in the low cluster are located on the Indonesian islands of Sumatra and Bali, and they are distinguished by the usage of Cash on Delivery (COD) and a limited number of employees in e-commerce businesses.